SIFAT DAN MUTU ARANG AKTIF DARI TEMPURUNG BIJI METE (Anacardium occidentale L.) - Dewi Alimah (Jurnal Penelitian Hasil Hutan, 2017)
Currently, cashew nut (Anacardium occidentale L.) shell is abundantly available as waste from chasew nut processing industries. Theoretically, cashew nut shell is potentially used for activated charcoal. This paper studies the properties and quality of activated charcoal made from cashew nut shell. The study also evaluates processing condition in producing optimum quality of activated charcoal. Initially, cashew nut shells were collected and carbonized in 500°C for 3 hours. Then, the charcoal was activated in temperatures of 800°C, 900°C and 1000°C for 30, 60 and 90 minutes. The data were then analyzed using analysis of variance and Tukey test for further significance test. Results show that chasew nut shell could potentially be used for commercial activated charcoal. The optimum quality of shell's activated charcoal was obtained by activating the charcoal in 1000°C for 90 minutes, that produced charcoal with properties of 0.40% moisture content, 8.85% volatile content, 77.40% fixed carbon content and 131.35 mg/g of methylene blue adsorptive capacity. Almost all charcoal's properties met the quality requirement stated in the Indonesian National Standar (SNI 06-37301995) except those of three properties: ash content (13.75%), benzene adsorptive capacity (2.93%) and adsorptive capacity of iodium (703.73 mg/g).